2020
DOI: 10.1111/echo.14660
|View full text |Cite
|
Sign up to set email alerts
|

The effect of successful parathyroid surgery on left ventricle function in patients with primary hyperparathyroidism evaluated with strain echocardiography

Abstract: Background: Hyperparathyroidism (PHP) is the most common cause of hypercalcemia in outpatients. It is characterized by many cardiac complications including chronic cardiac arrhythmia, hypertrophy, and diastolic insufficiency. However, there are insufficient data about the cardiac systolic function in PHP. Data regarding the positive effects of surgical treatment on cardiac complications are limited and inadequate. The aim of this study was to evaluate the postoperative changes in the left ventricle functions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…17 In another study, changes in the left ventricle functions were evaluated using strain echo in addition to traditional echocardiography in 22 PHPT patients following parathyroidectomy. 16 There were no statistically significant changes in the LVEF and other echo parameters post operatively at 6 months follow up. Even though GCS was not changed significantly following surgery; however, significant increase in GLS from 18.53 � 3.06 preoperatively to 20.25 � 3.89 were observed postoperatively (p < 0.004).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…17 In another study, changes in the left ventricle functions were evaluated using strain echo in addition to traditional echocardiography in 22 PHPT patients following parathyroidectomy. 16 There were no statistically significant changes in the LVEF and other echo parameters post operatively at 6 months follow up. Even though GCS was not changed significantly following surgery; however, significant increase in GLS from 18.53 � 3.06 preoperatively to 20.25 � 3.89 were observed postoperatively (p < 0.004).…”
Section: Discussionmentioning
confidence: 74%
“…There are few studies in the literature where Strain Echocardiography was used for the evaluation of LV function in PHPT patients. 6,16 Strain and strain rate echocardiography was concluded from color Doppler myocardial imaging and can estimate regional myocardial wall motion and its deformities. Strain describes the ratio of dimensional deformation in a tissue, and strain rate describes the degree of deformation.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary hyperparathyroidism may be associated with disease severity in congestive heart failure, especially in older, due to bone loss and osteoporosis (21). When the literature is reviewed, there may be a relationship between PTH levels and arterial stiffness, coronary atherosclerosis, abnormal left ventricular function (global longitudinal strain), LV asynchrony, brachial flow-mediated dilatation (bFMD) (adversely), especially in primary hyperparathyroidism; a regression in pulse wave velocity and improvement in global longitudinal strain with parathyroidectomy (22)(23)(24)(25). Although this finding could not be reached with primary hyperparathyroidism in a different study, improvements in pulse wave velocity were also observed using cinacalcet; a calcimimetic agent that provides a decrease in PTH levels in chronic renal failure and secondary hyperparathyroidism, in literature (26,27).…”
Section: Introductionmentioning
confidence: 99%